A crucial exosome-related gene pair (AAMP and ABAT) is associated with inflammatory cells in intervertebral disc degeneration - Ren, Huiyong; Li, Yumin; Liu, Hao; Fan, Jiaxin; Li, Jie; Li, Haopeng; Wei, Hongyu; Meng, Liesu; Cao, Shuai (Frontiers in Immunology, 2023)
Identification of exosome-related genes (ERGs) and competing endogenous RNAs (ceRNAs) associated with intervertebral disc degeneration (IDD) may improve its diagnosis and reveal its underlying mechanisms. We downloaded 49 samples from Gene Expression Omnibus and identified candidate ERGs using differentially expressed ERGs (De-ERGs), exosome-related gene pairs (ERGPs), and machine learning algorithms [least absolute shrinkage and selection operator (LASSO) and support vector machine (SVM)]. Immune cell-related ERGs were selected via immune-infiltration analysis, and clinical values were assessed using receiver operating characteristic curves. Based on the De-ERGs, a ceRNA network comprising 1,512 links and 330 nodes was constructed and primarily related to signal transduction pathways, apoptosis-related biological processes, and multiple kinase-related molecular functions. In total, two crucial De-ERGs [angio-associated migratory cell protein (AAMP) and 4-aminobutyrate aminotransferase (ABAT)] were screened from results in De-ERGs, ERGPs, LASSO, and SVM. Increased AAMP expression and decreased ABAT expression were positively and negatively correlated with CD8+ T cell infiltration, respectively. AAMP/ABAT was the only pair differentially expressed in IDD and correlated with CD8+ T cell infiltration. Furthermore, AAMP/ABAT displayed higher accuracy in predicting IDD than individual genes. These results demonstrated the ERGP AAMP/ABAT as a robust signature for identifying IDD and associated with increased CD8+ T cell infiltration, suggesting it as a promising IDD biomarker.